Avaliação ex-vivo da tolerância de cultivares da mamoneira (Ricinus communis L.) ao défict hídrico - Ana Paula de Faria (2010)
Water deficit is critical for plant development and productivity. Castor (Ricinuscommunis L.) oil is rich in ricinoleic acid (omega 9), a fatty acid widely used for medicinalpurposes, besides its great potential as a raw material for biodiesel production. This studyfocused on the biochemical and physiological screening of five castor bean cultivarsregarding the tolerance degree toward water deficit conditions. The relative water content(RWC), electrolyte leakage (EL), membrane damage index (MDI), lipid peroxidation andprotein oxidation were then investigated in leaf disks treated with PEG-6000 solutions at YWin the range of 0 to -2.4 MPa. All cultivars recovered at different extents from water deficitstress. BRS-Energia reached the best recovery percentage while BRS-Paraguaçu had poorlyrecovered. Maximum MDI was observed for BRS-Paraguaçu at YW of -1,8 MPa, a conditionthat slightly affected BRS-Energia and IAC-80 cultivars. Biochemical analyses showed thatcultivar IAC-80 exhibited the lowest levels of lipid hydroperoxides (LOOH), that remainedunaffected regardless the stress intensity. In contrast, LOOH levels BRS-Paraguaçu leavesdecreased when under severe water déficit. The protein oxidation levels in BRS-Energia was 50%lower than those for the cultivars IAC-80 and BRS-Paraguaçu under Yw of -1,8 MPa. Overall,these results indicate that, under our experimental conditions, BRS-Energia is the mosttolerant genotype to water deprivation; BRS-Paraguaçu is the most sensitive and IAC-80 fitsas an intermediate genotype.Keywords: castor bean, water deficit, relative water content, membrane damage index, lipidperoxidation, protein oxidation.